PENGEMBANGAN POTENSI KEWIRAUSAHAAN DALAM UPAYA PENINGKATAN PEREKONOMIAN MASYARAKAT DESA BLOKANG SERANG BANTEN - Stannia Cahaya Suci; Vadilla Mutia Zahara; Rah Adi Ginanjar; Cep Jandi Anwar (Bajang Institute, 2021)
The development of rural local potential is one part of national development efforts. Desa Blokang, Serang is located between the industrial area of Tangerang and Serang that has the potential its natural resources, one of them is bamboo plants, but this local potential has not been utilized properly by the community, the desire of its inhabitants to be able to increase local income is not accompanied by an understanding of production and local resource innovation. Therefore, the purpose of this event is to provide training and assistance for its people about the economic potential of the village and develop the potential by increasing entrepreneurship. The method used is by enlightenment to the community. The positive response was seen from the enthusiasm from the partisipants in following the material and increased understanding of the diversification of local food production and marketing of products via the internet. This provides hope for an increase in household and village income with existing entrepreneurial opportunities.